Doing real world research in sports studies (Routledge, 2014)
Traditional research methods textbooks tend to present an idealized and simplistic picture of the research process. This ground-breaking text however, features leading international sport researchers explaining how they actually carried out their real life research projects, highlighting the practical day-to-day problems, false starts and setbacks that are a normal part of the research process.